COMPARATIVE ANALYSIS OF DEPOSIT BETWEEN BANK MEGA AND BANK MUAMALAT - I nyoman Budiono; Abdul Hamid; Andi Kiki Patmawati; Nur Ainun Herawati Samad; Andi Dinul Islam Firdaus (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2026)
This study analyzes the fundamental operational differences of deposit products between conventional banking (Bank Mega) and Islamic banking (Bank Muamalat). Using a qualitative descriptive method, the study reveals that basic principles affect accessibility and cost structures for customers. Significant differences were found in minimum requirements and penalty consequences. Bank Mega sets a minimum balance for both regular and online account openings. Withdrawals before maturity incur a 1% penalty of the nominal amount and forfeiture of accrued interest. In contrast, Bank Muamalat, which applies the Mudharabah Mutlaqah principle, offers higher accessibility with a lower minimum. Early withdrawal fees are also lighter, being only a fixed account closure fee. Overall comparison shows similarities in aspects such as account opening/closing media, deposit term options, and the automatic renewal system. However, the core difference lies in the operational principles; Bank Mega is based on interest-based principles, whereas Bank Muamalat strictly applies Sharia principles.